2022
DOI: 10.1002/cjce.24594
|View full text |Cite
|
Sign up to set email alerts
|

Towards the development of a diagnostic test for autism spectrum disorder: Big data meets metabolomics

Abstract: Autism spectrum disorder (ASD) is defined as a neurodevelopmental disorder that results in impairments in social communications and interactions as well as repetitive behaviours. Despite current estimates showing that approximately 2.2% of children are affected in the United States, relatively little about ASD

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 48 publications
1
3
0
Order By: Relevance
“…Capping the number of input features at 5 maximizes the classifiers’ performance for this dataset while also minimizing potential overfitting concerns. This is also in line with the findings from Howsmon’s [ 30 ] and Qureshi’s study [ 42 ]. To validate the results of this feature selection, a similar procedure was carried out where the data were split the same way 1000 times and the combinations yielding the highest testing accuracy from each split were saved.…”
Section: Methodssupporting
confidence: 93%
See 1 more Smart Citation
“…Capping the number of input features at 5 maximizes the classifiers’ performance for this dataset while also minimizing potential overfitting concerns. This is also in line with the findings from Howsmon’s [ 30 ] and Qureshi’s study [ 42 ]. To validate the results of this feature selection, a similar procedure was carried out where the data were split the same way 1000 times and the combinations yielding the highest testing accuracy from each split were saved.…”
Section: Methodssupporting
confidence: 93%
“…Using that panel of seven metabolites, Howsmon was able to achieve a cross-validatory accuracy of 96.9% using LDA [ 30 ]. In a more recent study using the same dataset, Qureshi et al was able to achieve a cross-validatory accuracy of 97% using SVM and five metabolites [ 42 ]. Again, all features used in this classifier were present among the 11 identified by the factor analysis.…”
Section: Resultsmentioning
confidence: 99%
“…In ‘Towards the Development of a Diagnostic Test for Autism Spectrum Disorder: Big Data Meets Metabolomics,’ Fatir Qureshi and Jeurgen Hahn present their latest progress in their long‐term quest to improve autism spectrum disorder (ASD) diagnosing techniques. [ 2 ] This work is part of Prof. Hahn's personal quest to make ASD diagnostics more accurate, more specific, and more applicable in the earlier stages of a child's development. It is a challenging problem because ASD symptoms present differently from case to case.…”
Section: Using Pse Technology To Diagnose Autismmentioning
confidence: 99%
“…It is shown that one can determine with high accuracy if a sample came from a child with an ASD diagnosis, thereby offering the potential for biochemical tests to support an ASD diagnosis in the future. [ 1 ]…”
mentioning
confidence: 99%